Multisite Reproducibility of Results Obtained by Two Broth Dilution Methods for Susceptibility Testing of Mycobacterium avium Complex - Woods, Gail L. (American Society for Microbiology, 2003)
A multicenter study was conducted to assess the interlaboratory reproducibility of susceptibility testing of Mycobacterium avium complex (MAC) by broth microdilution using two different media (cation-adjusted Mueller-Hinton broth with 5% oleic acid-albumin-dextrose-catalase and 7H9 broth with casein) and by macrodilution using the BACTEC 460TB and 12B media at pH 6.8 and 7.3 to 7.4. Ten well-characterized strains of MAC (four macrolide susceptible, six macrolide resistant) were tested against clarithromycin and azithromycin (the latter only by BACTEC 460TB, pH 6.8). At each site, strains were tested against clarithromycin three times on each of three separate days (nine testing events per isolate) by using a common lot of microdilution trays and BACTEC 12B medium, pH 6.8; strains were tested once on three separate days against clarithromycin in 12B medium at pH 7.3 to 7.4 and against azithromycin. Agreement among MICs (i.e., mode ± 1 twofold dilution) was 100% for all strains and both drugs when BACTEC 460TB was used, regardless of the pH of the medium, but varied when microdilution with either medium was used, particularly with susceptible strains. Agreement based on interpretive category, with NCCLS-recommended breakpoints, was 100% for all strains with the BACTEC 460TB method (both drugs and both pH values) and with microdilution using 7H9 broth. With microdilution and Mueller-Hinton broth, agreement by interpretive category was 100% for eight isolates and >90% for two; errors occurred only in laboratories where personnel had minimal experience with this technique. MAC susceptibility testing may be performed by broth macrodilution or microdilution at either pH, with NCCLS-recommended interpretive breakpoints. However, because visual interpretation of broth microdilution end points is subjective, it is more prone to reader error; therefore, this method requires greater expertise than the BACTEC 460TB. Both techniques require appropriate validation and continued documentation of proficiency.